Minimizing Deductible Costs in Container Damage Claims to Control the Operational Reserve Budget: A Case Study of a State-Owned Cargo Handling Company - Prisma Rohman Wardana; Driana Leniwati; Nazaruddin Malik (Universitas KH. Abdul Chalim Mojokerto, 2026)
Managing deductible costs in container damage claims is a critical issue in maintaining the stability of a stevedoring company’s operational budget. This study aims to analyze strategies for controlling deductible costs through the integration of risk management, accounting information systems, and internal controls. Data were collected through in-depth interviews, observations, and documentation at PT Terminal Petikemas Surabaya, and then analyzed using the Miles and Huberman interactive model. The results indicate that deductible costs cannot be directly reduced because they are fixed, but they can be controlled by reducing the frequency of recurring minor claims. The lack of integration among risk, information, and control systems is the primary cause of cost inefficiency. Therefore, controlling deductible costs requires a systemic, integration-based approach to enhance operational efficiency and maintain the company’s financial stability.